Open Prison System in India: A Step Towards Reformation - Thakur, Manisha; Diwan, Promil (RESEARCH HUB International Multidisciplinary Research Journal, 2026)
In Indian Society, when any person has committed any kind of unlawful act then he is imprisoned in a prison as a prisoner and the society does not look at those prisoners with good eyes because the word prison itself creates a negative image within the society. But sometime, offences are committed without intention to commit such offence under a certain circumstance and just to protect such prisoners, the concept of open prison has been introduced as one of the major initiatives which marks as a reformation in prison system. The main objective behind the introduction of an open prison is to rehabilitate and reformate such prisoners by providing them some facilities such as minimal supervision, medical facilities, recreational facilities, family visit, remissions, and employment. So that he will come back in the society as a good human being and society will also accept him as a normal human being. This paper attempts to highlight the history and origin of open prison. Besides, the paper also explains the objectives of implementing an open prison system in India along with the constitutional provisions, eligibility criteria to access open prison and the judiciary pronouncements for establishment of more open jails.